Rebooting quarter-BPS operators in N $$ \mathcal{N} $$ = 4 super Yang-Mills - Agnese Bissi; Giulia Fardelli; Andrea Manenti (Journal of High Energy Physics, 2022)
Abstract We start a systematic study of quarter-BPS operators in four-dimensional N $$ \mathcal{N} $$ = 4 Super Yang-Mills with gauge group SU(N) making use of recently developed tools in conformal field theory. We adapt the technology of embedding space tensor structures in four dimensions to the problem of computing R-symmetry tensor structures, and we use the underlying chiral algebra to obtain the superconformal Ward identities. This allows us to fix the protected part of the four-point correlators, up to few ambiguities. As applications, we use the Lorentzian inversion formula to study the leading order OPE data in the large N supergravity limit and we make contact with the OPE limit of the five-point function of half-BPS operators.